Literature Review: Diferensiasi dan Pembelajaran Personal Dalam Kegiatan IPA - Sura Juddin; Dewa Dwi Pranahita (Indonesian Journal of Applied Science and Technology, 2025)
The diversity of students' abilities, interests, and learning styles presents a primary challenge in Science education. Traditional, one-size-fits-all approaches often fail to meet the needs of all learners optimally. Differentiation and personalized learning offer flexible, student-centered strategies tailored to individual needs to support the effective achievement of science competencies. This article examines the concepts of differentiation and personalized learning, their implementation strategies in science education, and literature findings regarding the effectiveness of both approaches on student motivation, conceptual understanding, and 21st-century skills. The study indicates that differentiating content, process, product, and the learning environment—coupled with interest-based personalized learning strategies—can enhance engagement, motivation, conceptual mastery, and critical thinking skills. These approaches are recommended as integral components of modern, inclusive science education aligned with the principles of the Kurikulum Merdeka (Emancipated Curriculum).